Althusser and Education Reassessing Critical Education - Backer, David I. (Radical Politics and Education, 2022)
Louis Althusser's thinking laid the groundwork for critical educational theory, yet it is often misunderstood in critical pedagogy, sociology of education, and related fields. In this open access book, David I. Backer reexamines Althusser's educational theory, specifically the claim that education is the most powerful ideological state apparatus in modern capitalist societies. He then presents this theory's flawed reception in critical educational research and draws out a lost tradition of educational thinking it inspired with important applications to race, gender, ideology, and the concept of social structure in education. Correcting the record about Althusser's thinking in the traditional narrative of critical educational research becomes an opportunity to revisit fundamental questions for thinking about school in its social context. For students and researchers of education, critical theory, sociology of education, and critical pedagogy, this book will be a resource for rethinking the social foundations of education, both as a field and as a set of theoretical frameworks for educational research. The eBook editions of this book are available open access under a CC BY-NC-ND 3.0 licence on bloomsburycollections.com.